Pengaruh Faktor Keperilakuan Organisasi Terhadap Kegunaan Sistem Akuntansi Keuangan Daerah (Studi Kasus pada Dinas di Kabupaten Karanganyar) - Rahmawati, Dita; , Dr. Zulfikar, SE, M.Si (2017)
This study aimed to examine the effect of behavioral factors organizational (clarity of purpose, training, supervisor support and utilization of information technology) of the regional financial accounting system utilities. This study uses behavioral factors as the organizational of independent variables and regional financial accounting system for dependent variables. The population is used as a sample is an civil servants who work finance section in Karanganyar regency government. This study uses a type of field research, with the type of data used are primary data obtained by distributing questionnaires to potential respondents on questions relating to the organization with behavioral factors influence of regional financial accounting system utilities. The result showed that the variables of clarity of purpose, supervisor support and utilization of information technology significantly effect the area of financial accounting system utilities, whereas training has no effect to usability region financial accounting system.